IMPLEMENTASI MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SD NEGERI 010 PULAU ARO - Yusmaneti Yusmaneti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is based on the low learning outcomes of Citizenship Education for fourth grade students of State Primary School 010, Pulau Aro, Kuantan Tengah Subdistrict, Kuantan Singingi Regency, from 12 students only 5 (41.66%) who achieved the minimum completeness criteria determined by the school at 70 with an average score amounting to 65.4. The research aims to improve the learning outcomes of Citizenship Education through the application of problem based intruction models. The results of the study show, during the learning process before using the problem-based learning model, the average score was 65.4 with incomplete categories and after using the learning model based on the average problem of student learning outcomes in the first cycle to 79.7 with complete categories while in the cycle II has increased again to 87.6 with complete categories. Based on the results of this study, it can be concluded that through the application of problem-based learning models (Problem Based Intruction) can improve Student Grade 4 Citizenship Education Learning Outcomes Primary School 010, Pulau Aro, Kuantan Tengah Subdistrict, Kuantan Singingi Regency.